Comparative Analysis of Dairy Farming Management and Business Model Between East Java and West Java, Indonesia - Jahroh, Siti; Atmakusuma, Juniar; Harmini; Fadillah, Achmad (Jurnal Manajemen dan Agribisnis, 2020)
Milk is an essential commodity because the Government of Indonesia aimed to increase domestic milk production up to 50% by 2020. At the present, domestic milk production in Indonesia is only able to fulfill 20% of national milk demand. East Java and West Java Provinces are the main producers of milk in Indonesia. The objective of this study was to compare dairy farming management and business model between East Java and West Java, Indonesia. This study employed descriptive statistical and quantitative analyses. The dairy farming management questionnaire survey was conducted in May-July 2016 and the dairy business model survey was conducted in October-November 2018. There were no significant differences in dairy farming activities between farmers in Lembang and Malang whereas the average number of lactating cows is 5 and 3 heads, respectively. Farmers received farm gate price of Rp4,622 per liter in Lembang and Rp4,535 per liter in Malang. Based on net return over cash variable cost, farmers in Malang and Lembang earned around 20 percent from the milk price. There were six inclusive business models (IBMs) identified between smallholder farmers, cooperatives, and private companies with different characteristics have been implemented in East Java and West Java. It is suggested that cooperative improves its role in the integrated agribusiness system in order to improve the bargaining position of dairy farmers as well as in terms of cost-efficiency. The strategies and policies should be implemented to support development of sustainable, profitable and smallholder-inclusive dairy supply chains in East Java and West Java. Keywords: inclusive business model, integrated agribusiness system, dairy farming, milk production, net return